Advances in accounting behavioral research. Vol. 21 - Karim, Khondkar E., 1961- (Emerald Publishing Limited, 2018)
Advances in Accounting Behavioral Research promotes research across all areas of accounting, incorporating theory from, and contributing knowledge to, the fields of applied psychology, sociology, management science, ethics and economics. Focusing on research that examines both individual and organizational behavior relative to accounting, the series provides a unique opportunity for the exchange of peer reviewed knowledge across all areas of accounting behavioral research and the development, discussion and expansion of theories from psychology, sociology and related disciplines. Advances in Accounting Behavioral Research encourages research that tests theory, explains theory, and develops theory that can be applied to better understand accounting domains. Accordingly, reviews of established theory and how that theory has and could be used in accounting are also strongly encouraged. Coverage includes, but is not restricted to: Individual judgement/decision making; Group decision making; Organizational behavior; Inter-organizational relationships; Technology integration; Strategic management/organizational theory; Theory development; Theory review; This volume includes chapters on emerging theory, methods, and applications towards behavioral research in accounting and audit.
Prelims -- The effect of mutual monitoring and need for achievement on budgetary slack in a team-based environment -- An empirical assessment of employee vs independent contractor status in taxation and the effects of judges' gender, political affiliation, and industry on those decisions -- Are non-professional investors' attitudes toward earnings management consistent with their investing behavior? -- Do consulting services performed by internal auditors influence their subsequent assessments when performing assurance services? -- Strategy evaluation when using a strategic performance measurement system: an examination of motivational and cognitive biases -- Stories vs statistics: the impact of anecdotal data on managerial decision making -- Index.
Includes index.
Print version record
Keywords: Accounting -- Psychological aspects; Business & Economics -- General; Finance & accounting